Division methods and selection principles for the ideal optical window of spectral beam splitting photovoltaic/thermal systems. (1st November 2021) - Li, Wenzhi; Abd El-Samie, Mostafa M.; Zhao, Shuang; Lin, Jianqing; Ju, Xing; Xu, Chao
Highlights: A comprehensive investigation of ideal optical windows (IOWs) for SBS-PV/T system. 3D numerical model precisely predicts system performance and thermal-economics. PV material spectral response method is convenient for determining IOW roughly. Optimal merit function and overall exergy efficiency methods are optimal choices. Basic selection principles for determining IOWs of SBS-PV/T systems are given. Abstract: Spectral beam splitting photovoltaic/thermal (SBS-PV/T) system has been attracting a lot of interest in its ability to achieve extremely efficient full-spectrum utilization of solar energy and co-generate electricity and thermal energy flexibly. The ideal optical window (IOW) is an essential concept in the SBS-PV/T system, splitting solar spectrum, and directly determining the ratio of electricity to thermal energy generated. In this work, 5 division methods (1, PV material bandgap division method; 2, Approximations of PV material spectral response method; 3, Spectral short-circuit current density method; 4, Optimal merit function method; 5, Optimal overall exergy efficiency method) for IOW have been reviewed and classified into three categories. Moreover, based on a 3-dimensional numerical model of the SBS-PV/T system, a systematic analysis and comparison of the aforementioned 3 types of methods were implemented under non-concentrated condition. Results showed that division method 2 is the best choice of IOW when considering system performance indicators, while division methods 4 and 5 are more suitable choices of IOW when considering thermal-economics. And, the divided bands of method 4 for Si solar cells show that energy balance model introduced comparatively big errors, the numerical modeling can predict IOW values of better accuracy. The IOW prediction results of the energy balance model introduced a maximum error of even 150 nm width. Substantially, the selection principles of different IOW division methods are provided, which is helpful for further development of SBS-PV/T systems.